Preparation and Microwave Absorption Properties of Polyaniline and Magnetite Core-Shell-Structured Hybrid - Xuan Zhang (International Journal of Polymer Science)
In this study, polyaniline and Fe3O4 (PAN@Fe3O4) hybrids are fabricated and their microwave absorption property is studied. PAN@Fe3O4 hybrids are fabricated by the in situ aniline polymerization at spherical of Fe3O4 which is prepared by the solvothermal process. Fourier-transform infrared spectrophotometer (FTIR), X-ray diffraction (XRD), and X-ray photoelectron spectroscopy (XPS) are applied to confirm the composition of the fabricated PAN@Fe3O4 hybrids. The morphologies of PAN@Fe3O4 hybrids are studied by scanning electron microscope (SEM) and transmission electron microscopy (TEM). The content of polyaniline in the PAN@Fe3O4 hybrids is calculated by thermogravimetric analysis (TGA). The magnetic properties of PAN@Fe3O4 hybrids are characterized by vibrating sample magnetometer (VSM). The microwave absorption property of PAN@Fe3O4 hybrids are measured on a vector network analyzer. The research show that the microwave absorptions property of the obtained PAN@Fe3O4 hybrids can be adjusted by controlling the in situ aniline polymerization at spherical of Fe3O4.